Pengaruh Konseling Individu dengan Pendekatan Rational Emotive Behavior Therapy terhadap Penyesuaian Diri Peserta Didik Kelas X - Wulan Eka Safitri (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
Adjustment is the ability of an individual to meet personal needs while responding to demands from the environment around them, so that a balance is achieved between the two. This allows individuals to create harmony with the existing reality. In SMA Muhammadiyah 01 Medan, it was found that there were students in class X who showed a low level of adjustment. This study applied the Quasi Experiment method with the Nonequivalent Control Group Design design. The sample involved in this study consisted of 10 students who were divided into two groups, namely 5 students in the experimental group and 5 students in the control group. Based on the results of the statistical test calculations, the t_count value was obtained as much as 7.270, and compared with the t_table at a significance level of 0.05 of 1.812. Since t_count ≥ t_table (7.270 ≥ 1.812) and the significance value (2-tailed) is less than 0.005 (0.000 ≤ 0.005), Ho is rejected and Ha is accepted. In addition, the average of the experimental group (95.20) is higher than the control group (82.40). This indicates a greater increase in the influence of counseling services in the experimental group compared to the control group. In other words, after students receive individual counseling with the Rational Emotive Behavior Therapy approach, there is a significant change in their ability to adjust. Based on these results, it is recommended that guidance and counseling teachers can implement this approach in counseling services to help students improve their ability to adjust.